Research trends in the field of sport impact on the economy: a bibliometric analysis - Marina Kudinska; Irina Solovjova; Žanete Korde (Frontiers in Sports and Active Living)
In this paper, the authors summarize the results of the bibliometric analysis. The object of the analysis is scientific publications published in the Scopus database in the scientific field of the impact of sports on the economy. The study aims to fill the research gap in the bibliometric analysis of the impact of sports on the economy by providing an empirical contribution that reveals trends in the scientific literature on the impact of sports on the economy, the most productive researchers, institutions, countries, journals in this field of research, and identifying a bibliometric framework that includes networks between researchers. Scientific articles indexed in Scopus were analyzed with no specific time limits using bibliometric analysis methods—performance analysis, citation analysis, and science mapping. We employed performance analysis, citation analysis, and science mapping via the Bibliometrix package R Studio® and the VOSviewer. The results of the systematic review show that, according to the Scopus database, 801 authors have studied the impact of sports on the global economy, and 299 scientific articles have been published in various journals around the world during the study period. This relatively low number suggests insufficient attention on the part of researchers to the importance of the sports sector. The most active researchers are from the USA, the UK, and China. The most influential journals and research institutions have been identified. The study results showed disagreement between the authors in some areas of the study (economic impact of major sporting events, impact of new sports infrastructure on regional economic growth, illustrating the ongoing debates in the field.